A better alternative to stratified permuted block design for subject randomization in clinical trials. (14th July 2014) - Zhao, Wenle; Friede, Tim; Henderson, Robin; Hougaard, Philip
<x xml:space="preserve">Abstract</x> Stratified permuted block randomization has been the dominant covariate‐adaptive randomization procedure in clinical trials for several decades. Its high probability of deterministic assignment and low capacity of covariate balancing have been well recognized. The popularity of this sub‐optimal method is largely due to its simplicity in implementation and the lack of better alternatives. Proposed in this paper is a two‐stage covariate‐adaptive randomization procedure that uses the block urn design or the big stick design in stage one to restrict the treatment imbalance within each covariate stratum, and uses the biased‐coin minimization method in stage two to control imbalances in the distribution of additional covariates that are not included in the stratification algorithm. Analytical and simulation results show that the new randomization procedure significantly reduces the probability of deterministic assignments, and improve the covariate balancing capacity when compared to the traditional stratified permuted block randomization. Copyright © 2014 John Wiley & Sons, Ltd.